Correlation and Relevance of Islamic Economic Theory and Modern Economics - Muhammad Yunus; Yadi Janwari; Ahmad Hasan Ridwan (al-Afkar, Journal For Islamic Studies, 2023)
This study aims to explain the correlation between economics and Islam. This research uses qualitative research, with a normative juridical approach and data collection techniques by means of literature study. The results of this study indicate that Islam is a perfect religion that regulates all aspects of human life including the economy. This is proven by the concept of welfare described in the Qur'an and Sunnah. Basically, the purpose of every human being's life is to achieve welfare, although humans interpret welfare from different perspectives. Most economic understandings assume that welfare is worldly material welfare. However, Islam defines welfare with the term Falah, which means holistic and balanced welfare between the material and spiritual dimensions. The Quran and Sunnah have taught that welfare will be achieved if humans live a life in balance between their material and spiritual lives. This is because human life does not only stop in this world, but there is still a second life that humans will face in the hereafter, and welfare will be achieved truly if humans can balance the needs of the world and the hereafter, and that is what is taught in Islamic economics